Innovation of baby food packaging using the implementation design with augmented reality technology and QR code / Muhammad Harrith Iqmal Md Razak ... [et al.] - Md Razak, Muhammad Harrith Iqmal; Omar, Mastura; Rosnan, Shalida; Zainuddin, Aezzaddin Aisyah; Mohd Lazim, Nur Aniza (Universiti Teknologi MARA, Kedah, 2023)
Packaging is designed to help boost product value by adding graphic aspects and making the package more functional. This is accomplished through the creation of packaging. An unsung hero of advertising and marketing, packaging is incredibly useful to protect, display, and sell the product. Its role in these processes is often overlooked. New forms of technology, such as Quick Response (QR) codes and Augmented Reality (AR), have been put to the packaging of Fawwaz Baby Food in order to convey information about the product. Use of QR codes and other forms of augmented reality innovation technology to increase interest in and enrolment in a Printing Technology course. Customers are able to quickly obtain information about the firm and the products they purchase simply by scanning a code that takes them directly to their Instagram accounts. This cutting-edge use of technology is awesome. The product packaging sachet needs to be shielded from any possibility that could lead to it becoming damaged, hence the primary objective of this packaging box is to fulfil that function. In addition, the goal of this innovative box for the product’s packaging is to make it simpler for consumers to store the goods in a limited amount of space and to enable customers to purchase the product using an innovation that has been developed. This creative design will also attract buyers’ attention due to the utilisation of vibrant hues and a colour scheme that appeals to both youngsters and adults. This packing box has perforations to make it easy for customers to retrieve the products contained within, and it may be reused without harming the unopened products.